Principles & practices of quality assurance : a guide for internal and external quality assurers in the FE and skills sector - Gravells, Ann. (SAGE : Learning Matters, 2016)
A guide for internal and external quality assurers in the FE and skills sector by best-selling author Ann Gravells.
Includes bibliographical references and index.
IQAC
Karim International
Keywords: Adult education -- evaluation